The Communist Political Culture: a Polyhedral, Complex and Conflictive Field - Rosano Alloza, Mario; Pérez Serrano, Julio (REVISTA DE HISTORIOGRAFÍA (RevHisto), 2024)
The objective of this article is to critically analyze the impact that the introduction of studies on political culture has had on the scientific production referred to the history of communism, which has allowed us to question the dominant stereotypes during the Cold War. The contributions made in the fields of history and social sciences, despite their diversity of approaches and methodologies, have made it possible to discard the image of the communist movement as an invariable, monolithic and essentially dystopian entity, which would have been condemned by the natural dynamics of the historical reality. At the same time, the limitations that, in the opinion of the authors, manifest many of these renovating proposals will also be pointed out and interpretative keys that could favor the development of studies on communism as an area of ​​interdisciplinary dialogue will be proposed.